Performance Comparison of Dymind DH-76 and Sysmex Xn-1000 Automated Hematology Analyzers - Pusparini Pusparini; Alvina Alvina (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
An automatic hematology analyzer is an essential instrument for the modern laboratory. A new hematology analyzer must undergo comparability testing with a currently used hematology analyzer. This study aimed to compare the performance of the Dymind DH-76 and Sysmex XN-1000 hematology analyzers. This study involved 96 EDTA blood samples from patients aged 18 to 85 years old at a hospital in Jakarta. A complete blood count was performed on each blood sample using two above-mentioned analyzers Dymind DH-76 and Sysmex XN-1000. The results from both instruments were compared by using the Pearson correlation test and the Passing-Bablok regression analysis to determine the agreement in performance between the two instruments. Between the Dymind DH-76 and Sysmex XN-1000, there was a high degree of agreement and correlation concerning the investigated parameters with r > 0.900 and p<0.001 for the parameters RBC, HGB, WBC, HCT, MCV, MCH, and neutrophil, monocyte, and eosinophil counts. The MCHC parameter had the values of r=0.797; p=0.0001, while the lymphocytes parameter had r=0.734 and p=0.0001. Only the basophils parameter showed a different result between the two aforementioned analyzers, with r=-0.179 and p=0.102. The majority of complete blood count parameters showed an excellent correlation and a high degree of agreement between the two instruments. The Dymind DH-76 hematology analyzer meets international standards (National Committee for Clinical Laboratory Standards/NCCLS) and can be used for hematological assay in the laboratory.